(untitled) (London Journal of Research In Science: Natural and Formal, 2023)
In this study, the curve number parameter is automatically determined in the micro-watershed of the Las Cañas stream of the Siscunsí paramo, in the department of Boyacá, Colombia, using the method of the Soil Conservation Service of the United States, which has the capacity to estimate the amount of runoff in an established hydrographic basin. This procedure is based on the use of geographic information systems, and thus create new maps of the curve number at regional scale, using algorithms of the same programs. Likewise, a multitemporal analysis of the vegetation cover and land use identified in the area was conducted to analyze the presence of anthropogenic activities such as agriculture, making it possible to evaluate the type of soil, precipitation, and flow rates. Finally, the results of the flow simulation obtained using GIS software were compared with the flows provided by the rational method based on the intensities calculated by the Dick Peschke and Frederich Bell models using historical precipitation records from climatic stations adjacent to the microbas in.